(untitled) (Research, Society and Development, 2020)
The growth of construction has contributed to a significant increase in the generation of urban waste. The inadequate disposal of this waste causes several environmental impacts. In this context, the use of urban waste as building materials is a viable and innovative technical alternative, being considered advantageous from a technical, economic and environmental point of view. This work aims to analyze the influence of the use of red ceramic waste (RCW) as a fine aggregate in the compressive strength (CS) and quantity Portland cement in concretes. For this, three different dosages were performed by the method of IPT / EPUSP, were produced with substitution of the fine aggregate by the red ceramic waste in the index 0%, 50% and 100%. This procedure was done for each of the three mixtures of the method. The results showed that, in comparison to the reference mixture, there was an increase in CS at 28 days and a decrease in Portland cement consumption. Thus, the red ceramic waste analyzed, is shown as an alternative material potentially viable to be used in concretes.